Espaço clandestino: a territorialização da pobreza em cidades médias brasileiras - Elias Coimbra Da Silva (Confins)
The text presented right here is an attempt to problematize the reproduction of certain spaces outsiders to the capitalist production of space, as well as the territorialities and reticularities involved in this dialectical process. Spaces of poverty, exclusion and vulnerability – the term and approaches are very varied – which require from geographers to look differently taking into account the specific characteristics of the same spaces. In order to actualize this attempt, we will consider some analysis’ proposals on the medium-sized cities of São Paulo in which irregular settlements – according to the legal term, but which we nominate «marginal territories» – presented. In the meantime we will propose another mode of understanding the concept of territory, the power relationships that permeate it and the exchange networks. Thus we hope to contribute to the understanding of socio-spatial inequalities, as like as to think about the advent of new actors in the processes of territorialization and production of urban space.